Life-cycle carbon footprint and total production potential of cross-laminated timber from California’s wildland-urban interface - Baishakhi Bose; Thomas P Hendrickson; Sarah L Nordahl; Seth Kane; Jin Fan; Sabbie A Miller; Corinne D Scown (Environmental Research Letters)
The frequency, scale, and severity of wildfires are steadily increasing in the Western United States. Sustainable forest management practices through forest thinning could reduce the impact of wildfires and provide lumber for wood-based, long-lived, and low-carbon building materials. This study explores the potential for harvesting biomass in California (CA) to mitigate wildfire risk and provide multi-decade carbon storage in the form of cross-laminated timber (CLT) for use in buildings. First, we assessed biomass resource availability, finding that the total live hardwood and live softwood available in the wildland-urban interfaces (WUIs) across CA sums to 14.1 million metric tons (MMT) and 34.9 MMT, respectively, which contains the equivalent of 90 MMT of atmospheric carbon dioxide. Then, we conducted a life cycle assessment of CLT considering softwood and hardwood sources to provide insights into emissions and energy demand associated with utilization of the wood removed for wildfire risk management. We found that the net life cycle carbon footprint of live hardwood and softwood when including biogenic carbon storage/emissions is 414 and 317 kg CO _2 e/m ^3 CLT, respectively. To incorporate the timing of these emissions and uptake, we have also conducted a cradle-to-grave time-dependent global warming potential (GWP) analysis. The time-adjusted GWP for live hardwood and live softwood is −227 and −104 kg CO _2 e/m ^3 CLT, respectively. In terms of total CLT production potential, 0.03 and 0.005 million m ^3 CLT can be sourced from live softwood and hardwood, respectively, in WUI on gentle slopes in CA. The resulting insights and approaches from this study are broadly applicable to other forested regions and WUIs across the US and the world, and provide a holistic approach to use forest thinning as a wildfire mitigation strategy in combination with a novel approach for life cycle assessment of building materials with a limited dataset.